2002
DOI: 10.1111/j.1945-5100.2002.tb01178.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of sticky interstellar organic material in the formation of asteroids

Abstract: Abstract-Collision experiments and measurements of viscoelastic properties were performed involving an interstellar organic material analogue to investigate the growth of organic grains in the protosolar nebula. The organic material was found to be stickiest at a radius ofbetween 2.3 and 3.0 AU, with a maximum sticking velocity of 5 m s-1 for millimeter-size organic grains. This stickiness is considered to have resulted in the very rapid coagulation of organic grain aggregates and subsequent formation of plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…To account for ice and organics present beyond the snow line we must recognize that the surface energy is significantly larger for these materials. The experiments by Kouchi et al (2002) and Kudo et al (2002) on organics and by Gundlach & Blum (2015) on water ice indeed show that both substances are significantly stickier than silica. It is thus reasonable to assume that the velocity range for growth as described above can be an order of magnitude higher, or 0.3 < ∼ v rel < ∼ 30 m s −1 (Wada et al 2009).…”
Section: Formation Of Cometesimalsmentioning
confidence: 75%
“…To account for ice and organics present beyond the snow line we must recognize that the surface energy is significantly larger for these materials. The experiments by Kouchi et al (2002) and Kudo et al (2002) on organics and by Gundlach & Blum (2015) on water ice indeed show that both substances are significantly stickier than silica. It is thus reasonable to assume that the velocity range for growth as described above can be an order of magnitude higher, or 0.3 < ∼ v rel < ∼ 30 m s −1 (Wada et al 2009).…”
Section: Formation Of Cometesimalsmentioning
confidence: 75%
“…The aggregates may be coated with a sticky organic material, observed on the surface of 67P's nucleus (Capaccioni et al 2015). This organic coating was observed on interplanetary dust particles collected in Earth's stratosphere (Flynn et al 2013); it can have a significantly higher tensile strength Kudo et al 2002) than is provided by van der Waals forces assumed in Equation (2). The GDS showers offer evidence of fragmentation of aggregates, suggesting that some junctions are not coated by organic material and are linked by van der Waals forces only.…”
Section: Particle Fragmentationmentioning
confidence: 98%
“…Kudo et al (2002) measured the temperature dependence of viscoelastic properties of molecular-cloud organic analogues prepared by mixing chemical reagents (as described in Kouchi et al 2002), and concluded that the aggregation of dust coated with molecular-cloud organic matter would be promoted at 200-300 K. However, there have been no further studies of the viscoelastic properties of organic matter, especially organic matter synthesized under molecular cloud conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions might also reflect the irradiation of organic compounds in the outer solar nebula (Chiang & Goldreich 1997;Ciesla & Sandford 2012). The remaining residue is hereafter referred to as DCOR, for Diffuse Cloud Organic Residue Kudo et al 2002).…”
Section: Introductionmentioning
confidence: 99%